Managing urban development process by using spatial information system: a case study of i-space - Abdullah, Alias; Abdullah, Muhammad Faris; Noordin, Mohamad Fauzan (MIP, 2003)
The advancement in Information and Communication Technology (ICT), particularly in relation to Geographical Information System (GIS), Computer Aided Design (CAD), Database Management System (DBMS), and Facility Management System (FMS), has provided the opportunity for urban government to adopt innovative and effective technologies to aid and improve the management and decision-making in urban development process.